Analysis of mechanism, properties and existing problems of liquid setting accelerators. Issue 16 (10th December 2022) - Ye, Fei; He, Biao; Tian, Chongming; Wang, Jian; Han, Xingbo; Song, Guifeng; Wang, Qinglong
Abstract: Setting accelerators play a vital role in the shotcreting of tunnel engineering because of their significant effect on the quality of shotcreting construction. Currently, several serious issues caused by improper use of setting accelerators are encountered in shotcreting, e.g. the loss of durability and strength of shotcrete, the corrosion damage to the environment and workers. Therefore, to overcome these problems induced by the use of setting accelerators, this paper develops a detailed description of the liquid setting accelerators, including the development history, classification, action mechanism, performance as well as its evaluation methods, and the current problems related to liquid setting accelerators in shotcreting. Specifically, this literature review aims to provide a comprehensive review of the action mechanism of each functional component in the liquid setting accelerators, the affect factors of the coagulation and strength properties of liquid setting accelerators, and the problems encountered when using liquid setting accelerators in practical engineering. To sum up, this review paper can provide new insights into the development of setting accelerators used in shotcreting and have constructive implications for the researchers involved.